Academic stress-induced changes in Th1- and Th2-cytokine response - Areej M. Assaf; Reem Al-Abbassi; Maysaa Al-Binni (Elsevier, 2017)
Psychological stress stimulates physiological responses releasing catecholamines and corticoids, which act via corresponding receptors on immune cells, producing a shift in the cytokine balance. These responses are variable depending on the nature of stressors. The effect of the academic stress on the production of the Th1-cytokines (TNF-α, IFN-γ, IL-1β, IL-2, IL-6 and IL-8) and Th2-cytokines (IL-1ra, IL-4, IL-5 and IL-10) on 35 medical/health sciences students after completing their questionnaires was investigated. Blood samples were taken at three stages; baseline stage at the beginning, midterm and final academic examination stages. Plasma cortisol and cytokines were measured during the three stages. The last two stages were compared with the baseline non-stress period. Results of the stress induced during the final examination stage were the highest with a significant increase in cortisol release, IL-4, IL-5 and IL-1ra release with a shift in Th1:Th2 cytokines balance towards Th2. Whereby, the midterm stage did not show significant reduction in Th1-cytokines except for TNF-α, with an increase in IFN-γ level that was reduced in the third stage. Th2 cytokine, IL-1ra, had positive correlations with Th1 cytokines; IL-2 and IFN-γ in the second stage and IL-6 cytokine in the third stage. Cortisol was positively correlated with IL-8 in the last stage and heart rates had negative correlation with IL-10 in the first and last stages. Findings of this study indicate that exam stress down-regulates Th1 with a selective up-regulation of Th2-cytokines. In conclusion, Cortisol might have a role in suppressing the release of Th1- mediated cellular immune response which could increase the vulnerability among the students to infectious diseases. Keywords: Academic stress, Cortisol, Th1-cytokines, Th2-cytokines, Medical/health sciences students